Analysis of light-emitting devices as optonegatrons - Filyniuk, M. A.; Shveikina, S. Ye. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Theoretical evaluation of light-emitting devices application as optonegatronic elements is carried out. The classification of optonegatronic is elaborated. Factors, influencing the origin of negative differential resistance in light-emitting devices are determined.